Attempt at the assessment of the infuence of the education on the level of knowledge of legal regulations concerning nursing profession among nurses - Zarzeka, Aleksander; Wawrzonkowska, Agnieszka; Panczyk, Mariusz; Belowska, Jarosława; Samoliński, Łukasz; Gotlib, Joanna (Polish Journal of Public Health, 2016)
Introduction. The profession of a nurse should be practised along with the standards of the most recent medical knowledge and law. Aim. The authors aimed at assessing the relationship between nurse’s education and their knowledge of the legal regulations, taking into account nurses’ performance at work. Material and methods. A total of 91 nurses were included in the study group. The mean age of the nurses was 34 years (min. 22, max. 63). Group 1: 32 nurses with medium-level education, group 2: 59 nurses with higher-level education. The study tool was a voluntary and anonymous survey questionnaire the authors’ own design, consisting 36 questions. The results obtained were subjected to statistical analysis using STATISTICA 10.0 (Medical University of Warsaw licence), nonparametric U Mann-Whitney Test α